2012
DOI: 10.1007/s10853-012-6574-0
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and tribological properties of graphene/poly(ether ether ketone) nanocomposites

Abstract: The tribological behavior of poly(ether ether ketone) (PEEK) composites was investigated using a universal micro-tribotester under dry friction conditions. We studied the effect of addition concentration, applied load, and sliding speed on the friction and wear behavior of composites filled with multi-walled carbon nanotubes (MWNTs), graphene oxide (GO) nanosheets, and c-aminopropyl trimethoxysilane-modified graphene oxide (GO-Si) nanosheets. The results showed that the friction reduction and anti-wear perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(55 citation statements)
references
References 32 publications
2
50
1
1
Order By: Relevance
“…[24][25][26]. Similar findings were reported for graphene, the use of which in different applications is growing extensively [27][28][29]. These two types of fillers (WS 2 -based and carbon-based) also represent two different, anticipated effects on the tribological properties, i.e., the WS 2 -based particles with great friction properties [30] are mostly expected to contribute to a lower coefficient of friction, while the carbon-based particles are supposed, due to their excellent mechanical properties [28], to mainly influence the wear resistance.…”
Section: Introductionsupporting
confidence: 80%
“…[24][25][26]. Similar findings were reported for graphene, the use of which in different applications is growing extensively [27][28][29]. These two types of fillers (WS 2 -based and carbon-based) also represent two different, anticipated effects on the tribological properties, i.e., the WS 2 -based particles with great friction properties [30] are mostly expected to contribute to a lower coefficient of friction, while the carbon-based particles are supposed, due to their excellent mechanical properties [28], to mainly influence the wear resistance.…”
Section: Introductionsupporting
confidence: 80%
“…It has also been shown that IL/MWCNTs composite can improve the friction reduction and the wear resistant ability as a friction modifier in IL because the composite may play the role of roller bearing during friction process [230]. Graphene, a two-dimensional sp 2 carbon atoms arranged in a honeycomb lattice, has attracted considerable attention due to its unique structure and remarkable properties, and the tribological applications of graphene have been reported [231][232][233][234][235][236][237]. Eswaraiah et al studied the tribological behavior of engine oil containing graphene as additive.…”
Section: Carbon Compoundsmentioning
confidence: 99%
“…Graphene, as a typical representative of two-dimensional atomic crystals, has been studied extensively in many fields of polymer composites. In tribological aspects, there have been many studies about the investigation of friction and wear behavior of polymer nanocomposites modified by graphene, and various polymer matrices such as phenolic resin, PPS, polyimide, UHMWPE, poly(ether ether ketone), epoxy, polydopamine, nylon have been studied [12][13][14][15][16][17][18][19][20][21][22] .…”
Section: Introductionmentioning
confidence: 99%